The influence of social influence, habit, and price value on use behavior of streaming applications among gen z using the utaut2 model - Kusumaningtias, Evita Nurliana; i Lestari, Wuryaningsih Dw (Jurnal Mantik, 2025)
This research, titled "The Influence of Social Influence, Habit, and Price Value on Use Behavior in Streaming Applications Among Gen Z Using the UTAUT2 Model (Case Study of Netflix, Viu, Disney)," employs a quantitative approach based on positivist philosophy, aiming to test hypotheses through statistical analysis. The study investigates the relationships between variables such as social influence, habit, and price value, and their impact on user behavior in streaming apps, specifically focusing on platforms like Netflix, Viu, and Disney. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model is used to analyze factors influencing technology adoption by incorporating constructs such as habit, price value, and social influence. Using purposive sampling, data was collected from 100 students, specifically those from the Management Program at the School of Economics and Business involved in the ornamental plant and fruit seedling business. The dependent variable, use behavior, measures app engagement, while independent variables include social influence, habit, and price value. Behavioral intention, the mediating variable, reflects commitment influenced by attitudes and social norms. Data was collected using closed-ended questionnaires with Likert scale items, and Structural Equation Modeling (SEM) was applied for analysis. The findings revealed that social influence had a positive but insubstantial impact on behavioral intention, while habit and price value had substantial positive effects. Behavioral intention positively influenced use behavior, while habit and price value also positively affected use behavior. Social influence and habit had no substantial impact on use behavior via behavioral intention, and price value had an insubstantial effect